2024
DOI: 10.15184/aqy.2024.29
|View full text |Cite
|
Sign up to set email alerts
|

Revised pre-Younger Dryas chronocultural sequence at the Pilauco site, north-western Patagonia (40°–44°S)

Antonio Pérez-Balarezo,
Mario Pino,
Ximena Navarro-Harris
et al.

Abstract: This project in southern Chile's Lake Region analysed late Pleistocene human–environment interactions. Two field seasons in 2020 and 2022 provided a new lithic collection dating to around 17 300–12 800 cal BP, which indicates human presence in north-western Patagonia prior to the Younger Dryas period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…Our findings are inconsistent with the chronological frame established for the earliest human occupation of southern South America, which had been proposed to date back to ~16,000 cal BP [ 27 , 107 110 ]. Remarkably, a new study [ 111 ] has shown reliable evidence of human occupations in Patagonia at 17.3 k cal BP indicating earlier dates for the initial peopling of southern South America. Despite traditional peopling models tending to support a later entry of humans to southern South America, it is not ruled out the possible presence of humans and their associated cultural evidence well before 16 Kya.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are inconsistent with the chronological frame established for the earliest human occupation of southern South America, which had been proposed to date back to ~16,000 cal BP [ 27 , 107 110 ]. Remarkably, a new study [ 111 ] has shown reliable evidence of human occupations in Patagonia at 17.3 k cal BP indicating earlier dates for the initial peopling of southern South America. Despite traditional peopling models tending to support a later entry of humans to southern South America, it is not ruled out the possible presence of humans and their associated cultural evidence well before 16 Kya.…”
Section: Discussionmentioning
confidence: 99%